A comprehensive resequence‐analysis of 250 kb region of 8q24.21 in men of African ancestry. Issue 6 (21st February 2014) - Chung, Charles C.; Hsing, Ann W.; Yeboah, Edward; Biritwum, Richard; Tettey, Yao; Adjei, Andrew; Cook, Michael B.; De Marzo, Angelo; Netto, George; Tay, Evelyn; Boland, Joseph F.; Yeager, Meredith; et al.
Abstract BACKGROUND Genome‐wide association studies (GWAS) have identified that a ∼1 M region centromeric to the MYC oncogene on chromosome 8q24.21 harbors at least five independent loci associated with prostate cancer risk and additional loci associated with cancers of breast, colon, bladder, and chronic lymphocytic leukemia (CLL). Because GWAS identify genetic markers that may be indirectly associated with disease, fine‐mapping based on sequence analysis provides important insights into patterns of linkage disequilibrium (LD) and is critical in defining the optimal variants to nominate for biological follow‐up. METHODS To catalog variation in individuals of African ancestry, we resequenced a region (250 kb; chr8:128, 050, 768–128, 300, 801, hg19) containing several prostate cancer susceptibility loci as well as a locus associated with CLL. Our samples included 78 individuals from Ghana and 47 of African‐Americans from Johns Hopkins University. RESULTS After quality control metrics were applied to next‐generation sequence data, 1, 838 SNPs were identified. Of these, 285 were novel and not yet reported in any public database. Using genotypes derived from sequencing, we refined the LD and recombination hotspots within the region and determined a set of tag SNPs to be used in future fine‐mapping studies. Based on LD, we annotated putative risk loci and their surrogates using ENCODE data, which should help guide laboratory studies. CONCLUSIONS In comparison to the 1000 Genome Project data, we have identified additional variants that could be important in establishing priorities for future functional work designed to explain the biological basis of associations between SNPs and both prostate cancer and CLL. Prostate 74:579–589, 2014. © 2014 Wiley Periodicals, Inc.